A Convenient Method for Synthesizing 1-Alkyl-2-acyl-sn-glycero-3-phosphoethanolamines - Okauchi, Tatsuo; Tsubaki, Kouta; Higuma, Yuri; Shimooka, Hirokazu; Kitamura, Mitsuru (Synthesis, 2024)
A convenient method for synthesizing 1-alkyl-2-acyl-sn-glycero-3-phosphoethanolamines (1-alkyl-2-acyl-GPEs) starting from an optical active alcohol is described. In this method, the phosphate group was introduced through the transesterification that we developed, and a protected 1-alkyl-2-lyso-GPE was employed as an intermediate. This compound is stable and serves as a common intermediate for the synthesis of various 1-alkyl-2-acyl-GPEs with different acyl groups.
Keywords: ether phospholipids; glycerophospholipids; phosphoethanolamines; transesterification; phosphorylation